Analisis Keberlanjutan Usahatani Sayuran Pada Lahan Pemakaman Di Kelurahan Maharatu Menggunakan Metode Multidimensional Scaling (MDS) (Jurnal Agribisnis Indonesia, 2026)
The demand for land for development continues to increase while land area remains limited. Conversion of agricultural land to non-agricultural use in urban areas has become a phenomenon in various cities in Indonesia which threatens the sustainability of farming. This research was conducted in Maharatu Village which utilizes cemetery land for vegetable farming, where the land will gradually diminish over time. This study aimed to determine the sustainability status of vegetable farming from ecological, economic, social, technological, and institutional dimensions, and to identify sensitive attributes affecting sustainability. The research used a descriptive qualitative method with purposive sampling involving 30 respondents. Data analysis to assess the sustainability index of vegetable farming used Multidimensional Scaling (MDS). The sustainability index and sensitive attributes were analyzed using the RAPS (Rapid Appraisal for Sustainability) method and leverage analysis. The sustainability index was calculated based on the ordination value of each analyzed dimension with a value range of 0–100, where 0–25 is categorized as unsustainable, 25.01–50 less sustainable, 50.01–75 moderately sustainable, and 75.01–100 highly sustainable. The results showed that the sustainability status of vegetable farming scored 65.46, categorized as moderately sustainable. Sensitive attributes include crop yield quality, soil fertility, pest and disease attack intensity, use of chemical fertilizers, farmer income diversification, farm income, land ownership status, selling price stability, marketing systems, farmer age and education, community views on land conversion, family participation, irrigation technology, planting patterns, post-harvest handling, use of information technology, superior seed technology, and availability of extension workers.